Ultrasound Versus Traditional Palpation to Guide Radial Artery Cannulation in Critically Ill Children: A Randomized Trial. (8th July 2017) - Anantasit, Nattachai; Cheeptinnakorntaworn, Pimporn; Khositseth, Anant; Lertbunrian, Rojjanee; Chantra, Marut
Abstract : Objectives: To identify success rates for radial artery cannulation in a pediatric critical care unit using either palpation or ultrasound guidance to cannulate the radial artery. Methods: A prospective randomized comparative study of critically ill children who required invasive monitoring in a tertiary referral center was conducted. All patients were randomized by a stratified block of 4 to either ultrasound‐guided or traditional palpation radial artery cannulation. The primary outcomes were the first attempt and total success rates. Results: Eighty‐four children were enrolled, with 43 randomized to the palpation technique and 41 to the ultrasound‐guided technique. Demographic data between the groups were not significantly different. The total success and first attempt rates for the ultrasound‐guided group were significantly higher than those for the palpation group (success ratio, 2.03; 95% confidence interval, 1.13–3.64; P  = .018; and success ratio, 4.18; 95% confidence interval, 1.57–11.14; P  = .004, respectively). The median time to success for the ultrasound‐guided group was significantly shorter than that for the palpation group (3.3 versus 10.4 minutes; P  < .001). Cannulation complications were lower in the ultrasound‐guided group than the palpation group (12.5% versus 53.3%; P  < .001). Conclusions: The ultrasound‐guided technique could improve the success rate and allow for faster cannulation of radial artery catheterization in critically ill children.